2021
DOI: 10.3390/ani11102947
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Distribution of Megamouth Shark, Megachasma pelagios, Inferred from over 250 Individuals Recorded in the Three Oceans

Abstract: The megamouth shark (Megachasma pelagios) is one of the rarest shark species in the three oceans, and its biological and fishery information is still very limited. A total of 261 landing/stranding records were examined, including 132 females, 87 males, and 42 sex unknown individuals, to provide the most detailed information on global megamouth shark records, and the spatial–temporal distribution of M. pelagios was inferenced from these records. The vertical distribution of M. pelagios ranged 0–1203 m in depth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Currently, Megachasmidae is considered to be an early-diverging lineage located outside the Lamnidae + Cetorhinidae clade within the Lamniformes [6]. After description and naming by Taylor et al [1], more than 200 individuals of megamouth sharks have been reported to date [7]. Increasing…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, Megachasmidae is considered to be an early-diverging lineage located outside the Lamnidae + Cetorhinidae clade within the Lamniformes [6]. After description and naming by Taylor et al [1], more than 200 individuals of megamouth sharks have been reported to date [7]. Increasing…”
Section: Introductionmentioning
confidence: 99%
“…Currently, megamouth sharks are listed as "Least Concern" on the IUCN Red List. They can reach 7 m in body length [10,11] and are found at various depths, ranging from the surface to 1500 m [7,10,13]. A possible segregation among different ontogenetic stages or between sexes as well as seasonal migrations are also recognized [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1976 to 2010 M. pelagios was considered rare, with only 50 individuals recorded globally during that time (Nakaya 2010). In recent years it is apparent that it is more common and widespread than previously thought, with 273 confirmed records to date across 16 countries in the Atlantic, Indian and Pacific Oceans (Yu et al 2021;Diez et al 2022;Skelton et al 2023). This species is classified as Least Concern on the IUCN Red List of Threatened Species, as it is globally distributed and does not appear to be heavily impacted by fisheries (Kyne et al 2019).…”
mentioning
confidence: 99%
“…The species reaches a maximum total length (TL) of 820 cm, while size at birth is thought to be less than 170 cm TL (Ebert et al 2021), based on the smallest individual recorded to date (176.7 cm TL, from northern Sumatra, Indonesia) (White et al 2004). However, most individuals recorded to date have been between 400 and 500 cm TL (Yu et al 2021). Until August 2020, M. pelagios was primarily recorded from the Pacific Ocean (n = 214 in the western Pacific and n = 35 in the eastern Pacific) with just six specimens each from the Atlantic and Indian oceans (Yu et al 2021).…”
mentioning
confidence: 99%